Research on the Cultivation of Oral Communication Under the Background of Culture and Tourism Communication - Yi, Wang; Selvarai Bexci, Manual (Journal of Theory and Practice in Education and Innovation, 2025)
In the context of the deep integration of culture and tourism, the role of oral communication professionals is no longer confined to being mere cultural disseminators but has expanded to become active promoters and key leaders in innovation within the tourism industry. Since the successful convening of the 18th National Congress of the Communist Party of China, it has repeatedly emphasized the extreme importance of cultural promotion and development for the overall national strategic layout at various propaganda, ideological, and cultural work conferences held nationwide. This series of important instructions clearly requires that all practitioners must attach great importance to the innovation of methods and approaches in their cultural and ideological propaganda work, actively utilizing modern new technologies and means to genuinely enhance the practical efficiency and broad influence of cultural dissemination. Currently, the integration of culture and tourism has become a new trend in the development of the tourism industry and an essential path for cultural inheritance and innovation. It not only injects new ideas and unique perspectives into the coordinated development of cultural promotion and the economy and society but also sets higher standards for the cultivation of oral communication professionals. Therefore, we must delve into more specific and detailed aspects to systematically and effectively cultivate high-quality oral communication professionals, particularly focusing on improving the oral skills of students majoring in broadcasting and hosting. To enhance communication skills, we must comprehensively strengthen the cultivation of cultural literacy and intercultural communication abilities. We should place great emphasis on practical training components in teaching, focusing on nurturing innovative capabilities under new media environments and a comprehensive attention to professional ethics and psychological qualities. In this process, we should be guided by market demand, closely align with the contemporary context, and meticulously design a more refined and scientific system for cultivating oral communication talents. This ensures that the talents we nurture can better adapt to the new requirements of cultural and tourism integration, contributing to the promotion of cultural prosperity and the upgrading of the tourism industry.